Three‐year follow‐up after psychotherapy for young people with bipolar disorder. (22nd December 2017) - Inder, Maree L; Crowe, Marie T; Moor, Stephanie; Carter, Janet D; Luty, Suzanne E; Frampton, Christopher M; Joyce, Peter R
Abstract : Objectives: (1) To examine the differences between interpersonal and social rhythm therapy (IPSRT) and specialist supportive care (SSC) in the longer term impacts of IPSRT and SSC on cumulative depression and mania symptoms over a further 78‐week follow‐up period post treatment. (2) To calculate the survival time before recurrence of a new mood episode over the 3‐year period. Methods: One hundred young people with bipolar disorder aged between 15 and 36 years who had been randomized to treatment with either IPSRT or SSC for 78 weeks were followed up for a subsequent 78 weeks. The Longitudinal Interval Follow‐up Evaluation was completed at 26‐week intervals. A Mann‐Whitney U test was used to determine if there were significant differences between therapy types and a Kaplan‐Meier survival analysis was used to determine time to recurrence. Cox regression was used to assess the association between time to relapse and therapy type. Results: There were no significant differences between therapies at each of the data points for either depression or mania scores. The mean change in depression and mania in both groups was significantly different for all three follow‐up data points. The actuarial cumulative recurrence rates were 53% for IPSRT and 49% for SSC. There was no significant difference between the groups in time to recurrence. Conclusions: While there were no significant differences between the two therapies, there was an overall reduction in symptoms in both therapies. There may be sustained benefits in providing intensive psychotherapies in conjunction with pharmacotherapy for young people with bipolar disorder.